El uso de los impulsos de entrenamiento (TRIMPS) para cuantificar la carga de entrenamiento en situaciones reducidas en balonmano - Ortega-Becerra, M. A.; Asian-Clemente, J. A.; Lopez-Adarve (Revista Ciencia del Deporte, 2016)
The aim of this study was to examine the internal load of use by a single parameter which includes the two basic components of the training load, volume, in the form of minutes, and intensity by the percentage of heart rate (HR), to determine the physical stresses to which are subject the reduced handball players in small-sided games. Subjects participated in three formats: a continuous format 8 minutes and 2 formats fractionated (2 periods of 4 minutes and 4 periods of 2 minutes) with the same ratio of work / rest of passive recovery between different periods (1: 1 /4). 12 male players (age 22.82 ± 4.77 years) belonging to the same team in the league participated in this study. Subjects were evaluated to assess the heart rate in the three formats. The results showed significant differences between formats, with the biggest beneficiary to continuous format, which seems the most appropriate format to meet the demands of handball. Evidence suggests that continuous format SSG induce greater internal loads in players compared to intermittent SSG format and that should help coaches to establish a better distribution of play according to their objectives.